Reforming the governance of the International Monetary Fund - Kelkar, Vijay (2004)
Traces the emergence of a 'democratic deficit' within the governance structure of the Fund i.e. the 'quota regime'. Proposes a set of principles to reform the quota regime. Provides a sketch of the pattern of governance that might characterise the fund if the quota regime is reformed.